Assessing posttraumatic stress related impairment and well-being: The Posttraumatic Stress Related Functioning Inventory (PRFI). (January 2016) - McCaslin, Shannon E.; Maguen, Shira; Metzler, Thomas; Bosch, Jeane; Neylan, Thomas C.; Marmar, Charles R.
Abstract: Posttraumatic stress symptoms are associated with poorer social and occupational functioning and quality of life. However, general assessments of functioning do not determine the extent to which these difficulties are directly related to PTSD symptoms. This study examines the psychometric properties of a self-report measure, the 27-item Posttraumatic Stress Related Functioning Inventory (PRFI), which was developed to provide a self-report tool for clinicians and researchers to better understand the perceived impact of PTSD symptoms on functioning. The psychometric properties of the PRFI were examined utilizing data collected within a larger study examining quality of life and functioning in 251 veterans who had served in OEF/OIF/OND and endorsed the presence of subsyndromal or greater levels of PTSD symptoms at screening. One-year test-retest reliability of the measure was examined in a subset of the baseline sample who received a second administration of the PRFI ( n  = 109). Higher levels of PTSD symptoms were associated with poorer functioning in all domains. The PRFI demonstrated convergent validity with a measure of PTSD symptoms and was less correlated with measures of alcohol and drug use, good internal consistency and test-retest reliability from baseline to one-year follow-up. The PRFI provides self-report information regarding several domains of functioning. This initial examination of psychometric properties of the scale indicated that it may be useful for efficiently eliciting information about the ways in which PTSD symptoms in veterans impact everyday functioning. Highlights: This study examines a novel measure of PTSD related functional impairment. Findings indicate that the measure has acceptable validity and reliability. The measure can be used in a time-efficient fashion to assess impairment. This measure can be useful for guiding further assessment and treatment.